The Woman Worker, 1926-1929 - Hobbs, Margaret (Margaret Helen); Sangster, Joan; Canadian Committee on Labour History (Canadian Committee on Labour History, 1999)
This volume presents the inaugural issue and articles from The Woman Worker, the official newspaper of the Canadian Federation of Women's Labor Leagues, during its 1926 to 1929 run. Edited by prominent Communist Party of Canada leader Florence Custance, The Woman Worker's objective was to "champion the Protection of Womanhood, and the cause of the Workers generally." In this collection, Hobbs and Sangster have provided an introductory chapter examining the evolution The Woman Worker, its editor Florence Custance, the Communist-led Women's Labor Leagues, and, more generally, the socio-economic and political context of the mid to late 1920s. Each chapter includes an introduction and suggestions for further reading. Chapters include women and wage work, protective legislation, feminism and social reform, peace and war, women and the sex trade, marriage, the family and domestic labour, and the local Women's Labor Leagues at work. –Publisher's description
https://archive.org/details/womanworker192610000unse
Keywords: 20th century; Canada; Employment; Employment History Sources; History; History Sources; Social conditions; Social conditions Sources; WOMEN labor union members; Woman worker (Toronto; Ont.); Women; Women employees